2017
DOI: 10.1093/ageing/afx006
|View full text |Cite|
|
Sign up to set email alerts
|

A closer look at the trajectory of physical functioning in chronic hemodialysis

Abstract: very few hemodialysis patients maintain a good physical condition over a 2-year time span. Especially in older patients, physical performance is poor and decline is faster than in the healthy population. These findings should be taken into account when considering dialysis in older patients and more emphasis should be placed to attempts for improving physical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…van Loon et al . [ 131 ] also demonstrated that physical performance declines while on haemodialysis, especially for older patients. These reports appear at odds with a study by John et al .…”
Section: How Should We Care For the Frail Patient With Ckd?mentioning
confidence: 99%
“…van Loon et al . [ 131 ] also demonstrated that physical performance declines while on haemodialysis, especially for older patients. These reports appear at odds with a study by John et al .…”
Section: How Should We Care For the Frail Patient With Ckd?mentioning
confidence: 99%
“…For inpatients, the mean age was 55 years in this study, which was younger than 65 years reported from Sweden [15]. Elderly dialysis patients could have more age-related comorbidities, such as atherosclerosis and diabetes mellitus, increased levels of frailty and malnutrition, higher risk of cognitive dysfunction, which may contribute to poor physical performance and clinical outcome compared to younger patients [16,[19][20][21][22][23][24]. Second, glomerulonephritis was the leading cause of ESKD in China, while diabetes and hypertension were more common in the USA, European countries, and some other counties in Asia [6,10,11,[14][15][16]25].…”
Section: Discussionmentioning
confidence: 64%
“…Despite the association between haemodialysis (HD) and a rapid decline in physical and cognitive function, many older comorbid patients default onto HD. 1,2 The Frail Elderly Patient Outcomes on Dialysis (FEPOD) study demonstrated quality of life (QOL) is similar on HD and assisted peritoneal dialysis (asPD) with frailty being the principal association with QOL, 3 but better treatment satisfaction with asPD, which was predominantly delivered as healthcare-assisted automated PD (APD). An extension of the FEPOD trial showed better symptom control in patients on asPD compared to those on conservative care with similar kidney treatment satisfaction scores.…”
Section: Introductionmentioning
confidence: 99%